2012
DOI: 10.1371/journal.pone.0040762
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Modulates Expression of Human Rhinovirus-Induced Airway Epithelial Host Defense Genes

Abstract: Human rhinovirus (HRV) infections trigger acute exacerbations of chronic obstructive pulmonary disease (COPD) and asthma. The human airway epithelial cell is the primary site of HRV infection and responds to infection with altered expression of multiple genes, the products of which could regulate the outcome to infection. Cigarette smoking aggravates asthma symptoms, and is also the predominant risk factor for the development and progression of COPD. We, therefore, examined whether cigarette smoke extract (CSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 39 publications
9
64
0
Order By: Relevance
“…IFN protein has been observed to vary with different RV subtypes and much lower levels of RV16-induced IFN-β protein have been reported6 19 since the original report 7. Other investigators have failed to detect RV16-induced IFN-β protein production despite significant mRNA induction,4 22 suggesting that bronchial epithelial cells may vary in their response to RV infection.…”
Section: Discussionmentioning
confidence: 99%
“…IFN protein has been observed to vary with different RV subtypes and much lower levels of RV16-induced IFN-β protein have been reported6 19 since the original report 7. Other investigators have failed to detect RV16-induced IFN-β protein production despite significant mRNA induction,4 22 suggesting that bronchial epithelial cells may vary in their response to RV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Human RV-16 was propagated as described 23 . Bronchial epithelial cells were exposed to HRV-16 at 10 5.5 50% tissue culture-infective dose (TCID 50 ) U/ml (MOI of ~1) 24 .…”
Section: Methodsmentioning
confidence: 99%
“…In COPD and smokers without COPD, a variety of studies have shown that cigarette smoke exposure impairs host defence by decreasing epithelial barrier function, ciliary function, antimicrobial peptide production and antiviral responses, while increasing mucus production (59;76;89). Cigarette smoke is the main risk factor for development of COPD, and many of these epithelial features of COPD can be explained by a direct or indirect result of cigarette smoke exposure.…”
Section: Epithelial Cell (Dys)function In Inflammatory Lung Diseasesmentioning
confidence: 99%